Spatial-temporal distribution and transport flux of polycyclic aromatic hydrocarbons in a large hydropower reservoir of Southeast China: Implication for impoundment impacts. (February 2020) - Wu, Yuling; Wang, Xinhong; Ya, Miaolei; Li, Yongyu; Liu, Yihao; Chen, Hanzhe
Abstract: In order to investigate the impacts of dam-related water impoundment on the spatial-temporal variations and transport of anthropogenic organic pollutants, 15 priority polycyclic aromatic hydrocarbons (PAHs) were analyzed in water samples from the Shuikou Reservoir (SKR) of the Minjiang River. The SKR was formed after the construction of the Shuikou Dam, which is the largest hydropower station in Southeast China. The water samples were collected from the backwater zone of the SKR, in both the wet and dry seasons, corresponding to the drainage and impoundment periods of water flow, respectively. The concentrations of the dissolved PAHs in surface water from the wet season (average of 161 ± 97 ng L −1 ) were significantly higher (ANOVA, p < 0.01) than those from the dry season (average of 43 ± 21 ng L −1 ). PAH concentrations in the SKR decreased from upstream (industrialized cities) to downstream (rural towns or counties), indicating high PAH loads caused by intensive urbanization effects. The high proportions of 3-ring PAHs in the wet season were from local sources via surface runoff; while the elevated proportions of 4- to 6- ring PAHs in the dry season reflected atmospheric deposition emerged of these PAHs and/or volatilization of 3-ring PAHs enhanced. Molecular diagnostic ratios of PAH isomers in multimedium and principal component analysis indicated that PAH presence in the SKR was mainly attributed to pyrogenic origin. The isomeric ratios of fluoranthene to fluoranthene plus pyrene in the wet season were homogeneous, implying that there were continuous new inputs along the riverine runoff. However, these ratios showed spatial downward trend in the dry season, indicating continued degradation of PAHs occurred along the transport path during the impoundment period. The input and output fluxes of PAHs in the SKR were 5330 kg yr −1 and 2991 kg yr −1, revealing that the reservoir retained contaminants after impoundment of the hydropower dam. Graphical abstract: Image 1 Highlights: PAHs in the Shuikou Reservoir presented a low-middle level and latent eco-environmental risk. Predominantly pyrogenic PAHs were closely related to regional urbanization in the reservoir. Spatial variations of PAHs reflected the accumulation effect of pollutants in reservoir dam. PAHs underwent discrepant transport processes during different water impoundment periods. Impoundment flux of PAHs showed the reservoir dam could cause pollutant retention. Abstract : Impoundment of the hydropower dam can reduce the transport and cause retention of PAHs in the reservoir river.